EFFECT OF AZOTOBACTER AND AZOSPIRILLUM ON GROWTH AND YIELD OF RICE GROWN ON TIDAL SWAMP RICE FIELD IN SOUTH KALIMANTAN - Fakhrur Razie; Iswandi Anas (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
Tidal swamp land is a potential area for rice cultivation. However, tidal swamp is fragile ecosystems, so that when this area is used for rice cultivation, it has to be done carefully. To reduce a risk of environmental pollution in the tidal swamp area due to rice cultivation, the area should be managed properly and wisely especially when using agrochemicals such as fertilizers and pesticides. In relation to this, the use of bio-fertilizer such as Azotobacter or/and Azospirillum, an atmospheric nitrogen fixing bacterium, might be an important thing for this area. The objectives of this study were to evaluate the number of NFB (i.e. Azotobacter and Azospirillum spp.) found in tidalswamp rice fields of South Kalimantan, and their ability in fixing atmospheric nitrogen and supplying this fixed nitrogen to rice, and in increasing rice yields. There were three research stages performed in this study. The first, collecting, isolating and purifying the NFB on the selective media of nitrogen free media. The second, a hydroponic experiment in the greenhouse using Yoshida nutrition solution (Yoshida et al., 1976 in IRRI, 2003) as culture media and selected Azotobacter and Azospirillum. The third experiment was to study the effect of selected Azotobacter isolates to increase growth and yield of IR64 and Margasari rice cultivars, and two Azotobacter isolates were combined with six inoculation methods for Siam Unus rice cultivar as treatments. The result showed that the number of NFB strains found in rhizospere rice cultivars were varied widely. Then, Azotobacter and Azospirillum spp selected from rice fields in the tidal land of South Kalimantan when associated with IR64 and Siam Unus rice cultivars have ability in fixing atmospheric N2 and in supplying N on the initial rice growth. Azotobacter T.B.PDST.2b and T.HM.BPMT.2b were significantly supplying N for early growth of IR64 rice cultivars (2.34 and 2.13 %N). The ability of these isolates to fix atmospheric N2 was similar to N fertilizer (urea) in supplying N (2.2% N). Only Azotobacter T.B.PDST.2b was relatively significant to supply N (1.36% N) for Siam Unus rice cultivar early growth, even though this strain has less ability than N fertilizer (1.94% N) in supplying N. Azotobacter isolates grow in media containing no urea were higher IAA produced than in media containing Urea. Furthermore, yield of IR64, Margasari and Siam Unus inoculated with Azotobacter isolates were 3.87–4.93; 4.63-5.36 and 5.44-6.42 ton/ha respectively. In conclusion, the utilization of Azotobacter and Azorpirillum spp to substitute N fertilizer would be able to increase effeciency of N nutritions and to avoid environment pollutions risks from agrochemical N fertilizer other than to increase rice yields on tidal land of South Kalimantan.Keywords: Azotobacter, Azospirillum, rice cultivars, tidal lands and rice yields.